EFFECT OF ABLATION ENVIRONMENT ON THE CHARACTERISTICS OF GRAPHENE NANOSHEETS PRODUCED BY LASER ABLATION - VAGHRI, Elnaz; DORRANIAN, Davoud (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The effect of ablation environment on the characteristics of graphene sheets produced by the laser ablation method in liquid medium has been studied experimentally and reported here. Graphene sheets were synthesized by using Q-switch Nd-YAG laser at 532 nm wavelength and 7 ns pulse width and laser fluence of 0.5 J/cm2 in liquid nitrogen and distilled water environments. The structure and morphology of the ablation products are characterized by X-ray diffraction method, UV-Visible absorption spectroscopy, transmission electron microscopy (TEM), Raman and Fourier transform infrared spectroscopy (FTIR). Results indicate that the graphene nanosheets synthesized by the laser ablation method in liquid nitrogen environment have larger sp2 carbon domains and minor structural defects. Therefore, in our experimental conditions, the liquid nitrogen environment seems to be a better medium for producing graphene sheets with high quality, in comparison with the water.